2006
DOI: 10.1007/s10038-005-0348-3
|View full text |Cite
|
Sign up to set email alerts
|

Mutational screening of the RB1 gene in Italian patients with retinoblastoma reveals 11 novel mutations

Abstract: Retinoblastoma (RB, OMIM#180200) is the most common intraocular tumour in infancy and early childhood. Constituent mutations in the RB1 gene predispose individuals to RB development. We performed a mutational screening of the RB1 gene in Italian patients affected by RB referred to the Medical Genetics of the University of Siena. In 35 unrelated patients, we identified germline RB1 mutations in 6 out of 9 familial cases (66%) and in 7 out of 26 with no family history of RB (27%). Using the single-strand conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
20
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 38 publications
4
20
0
Order By: Relevance
“…In a recent paper appeared on the Journal of Human Genetics, Sampieri and Coll., 82 having found a mutation rate of 37% in a series of Italian patients with 'hereditary retinoblastoma', conclude that: 'The mutation rate reported in the study is quite similar to that found by other groups using the same methodological approach' and that, given the disappointing results of this investigation, '. .…”
Section: Discussionsupporting
confidence: 84%
“…In a recent paper appeared on the Journal of Human Genetics, Sampieri and Coll., 82 having found a mutation rate of 37% in a series of Italian patients with 'hereditary retinoblastoma', conclude that: 'The mutation rate reported in the study is quite similar to that found by other groups using the same methodological approach' and that, given the disappointing results of this investigation, '. .…”
Section: Discussionsupporting
confidence: 84%
“…The majority of germline mutations that have been identified in patients with hereditary retinoblastoma are nonsense or frameshift mutations, mostly located in the exons 1-25 of the RB1 gene (Sampieri et al, 2005). These kinds of mutations will lead to abortive transcripts that will be degraded, leaving only the transcript of the normal allele.…”
Section: Rb1 Gene Mutation In Retinoblastomamentioning
confidence: 99%
“…2 Penetrance and expressivity of hereditary RB may depend on the type of inherited mutation, and can vary even within families and among patients with identical mutations. [3][4][5] This indicates a role of modifiers that may affect genome stability to favor the occurrence of somatic mutations, and/or the apoptotic pathway to induce loss or maintenance of the mutated retinoblasts.The p53 pathway, the master control system of these processes, is controlled by a feedback autoregulatory loop in which p53 transcriptionally activates MDM2, that in turn functions as a negative regulator by promoting the proteolytic degradation of p53. Interestingly, this circuit can also target pRB to degradation and in physiological condition controls the cell cycle and apoptosis of the retinal cone precursors, from which the RB cell lineage originates.…”
mentioning
confidence: 99%
“…2 Penetrance and expressivity of hereditary RB may depend on the type of inherited mutation, and can vary even within families and among patients with identical mutations. [3][4][5] This indicates a role of modifiers that may affect genome stability to favor the occurrence of somatic mutations, and/or the apoptotic pathway to induce loss or maintenance of the mutated retinoblasts.…”
mentioning
confidence: 99%